Source-oriented variation in trace metal distribution and fractionation in sediments from developing aquaculture area—A case study in south Hangzhou bay, China. Issue 1 (15th December 2017) - Mao, Lingchen; Ye, Hua; Li, Feipeng; Tao, Hong; Shi, Liu; Chen, Ling; Shi, Weiling; Yan, Geng; Chen, Hao
Abstract: Elevation in toxic trace metal concentration found in coastal sediments in recent years (2013–2016) increased the risk to the aquaculture industry in south Hangzhou bay. This study assessed the main factors controlling the metal distribution and mobility in sediments by sampling from 20 sites along the bank. Spatial distribution and cluster analysis indicated that Cd, As, Hg and Sb attributed to anthropogenic terrestrial sources; while Cr, Co, Cu, Ni, Zn, and Pb, carried by fine-grained sediments and accumulated on tidal flat, were inputted from marine sources. High mobility of Cd was expected because of its considerable proportion ( 50%) associated with the acid extractable fraction. Pb, Cu and Co in redox sensitive fraction should also be taken into concern in management of reclaimed area affected by tide. Risk assessments by potential ecological risk index (PERI) emphasised the importance of further monitor and proper treatment of 4 terrestrial generated metals in sediments. Highlights: Considerable amount of acid extractable Cd made it highly mobile in sediments. Fine-grained sediments from the outer bay elevated metal contents on tidal flat. Pb, Cu and Co in redox sensitive fraction increased risk on reclaimed area. Accumulation of emerging metal Sb in sediment increased the ecological risk.